Medication Errors in Administration of Chemotherapeutic Agents: an Observational Study: Medication Errors in Administration of Chemotherapeutic Agents - Maria Tavakoli-Ardakani; Somayeh Omidi; Azadeh Eshraghi; Jamshid Salamzadeh (Iranian Journal of Pharmaceutical Sciences, 2013)
Chemotherapy medication errors may lead to potentially harmful consequences while most of them could be preventable. This study aims to determine the incidence and type of drug handling and administration errors among the nurses and to identify possible contributing factors. Setting of the study was a teaching hospital affiliated to Shahid Beheshti University of Medical Sciences, Tehran, Iran. To attain the study objectives, an observational, cross-sectional study was performed in the haematology and oncology wards of the hospital. A checklist consisting of appropriate process of handling, preparation and administration of injectable chemotherapy agents was developed and used by a trained pharmacist. In addition, socio-demographic characteristics of nurses were recorded. The primary outcome was the number and type of medication errors in chemotherapy administration according to the prepared check lists. Overall, administration processes of 544 chemotherapy medications, consisting of 8322 error opportunities, were observed of which 2705 (32.5%) errors were detected. 52.8% (2926/5532), 15.5% (254/1635) and 26.5% (306/1155) of the errors were in the handling, preparation and injection stages, respectively. The top 5 drugs with the highest risk of errors were metotraxate 45.4% (20/44), fluorouracil 38.5% (439/1139), cyclophosphamide 37.1% (267/719), vincristine 34.8% (240/689) and etoposide 33.5% (125/373). Our results revealed a substantial occurrence rate of medication errors during preparation and administration of injectable chemotherapy agents, which are often made by nurses who fail to follow relevant nursing standards. This confirms that educational programs and advanced pharmaceutical care services are required for safe preparation and administration of intravenous chemotherapy agents.